Post‐traumatic growth in survivors of allogeneic hematopoietic stem cell transplantation. Issue 8 (10th November 2014) - Jeon, Mijin; Yoo, Il Young; Kim, Sue; Lee, Jehwan
Abstract Objective This study aimed to understand factors related to post‐traumatic growth (PTG) in patients who received allogeneic hematopoietic stem cell transplantation (HSCT), building baseline data for developing intervention programs to enhance PTG in HSCT survivors. Methods A self‐report survey was administered to 100 patients who received HSCT within the last 5 years. The Post‐traumatic Growth Inventory, Impact of Event Scale—Revised, Perceived Social Support Scale, and Healthcare Professional's Support Scale were used, as well as items on demographic and clinical characteristics. Standard deviations of frequency and percentage, Chi‐squared test between genders, independent t‐test, correlation analysis between independent variables and extent of PTG, and regression analysis were conducted. Results The PTG levels of HSCT survivors were statistically significantly higher when participants were women, carried out more religious activities, had higher educational levels, or utilized nurse counseling. The 'intrusive thinking' traumatic impact subcategory, as well as social support and support from healthcare professionals, were found to be highly related to PTG scores. Upon multiple regression analysis, factors with greatest influence on PTG in HSCT survivors were support from healthcare professionals, followed in order, by social support, utilization of nurse counseling, intrusive thinking, and frequency of religious activities. Conclusions We suggest implementing programs for HSCT patients to enhance support from healthcare professionals and to increase post‐traumatic growth through greater utilization of nurse counseling, self‐help meetings, and writing. Copyright © 2014 John Wiley & Sons, Ltd.